2021
DOI: 10.7554/elife.67577
|View full text |Cite
|
Sign up to set email alerts
|

Broad geographic sampling reveals the shared basis and environmental correlates of seasonal adaptation in Drosophila

Abstract: To advance our understanding of adaptation to temporally varying selection pressures, we identified signatures of seasonal adaptation occurring in parallel among Drosophila melanogaster populations. Specifically, we estimated allele frequencies genome-wide from flies sampled early and late in the growing season from 20 widely dispersed populations. We identified parallel seasonal allele frequency shifts across North America and Europe, demonstrating that seasonal adaptation is a general phenomenon of temperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 103 publications
9
107
3
Order By: Relevance
“…Our results are mostly in line with Kapun et al (2016) , who also described significant seasonal differences in In(2R)NS and In(3R)P , but not In(3R)Mo , from eastern US populations. Whereas, Machado et al (2021) analyzed the association between seasonally variable SNPs and inversion breakpoint regions, finding significant associations for In(2L)t and for a set of three inversions on arm 3R, but not for In(2R)NS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are mostly in line with Kapun et al (2016) , who also described significant seasonal differences in In(2R)NS and In(3R)P , but not In(3R)Mo , from eastern US populations. Whereas, Machado et al (2021) analyzed the association between seasonally variable SNPs and inversion breakpoint regions, finding significant associations for In(2L)t and for a set of three inversions on arm 3R, but not for In(2R)NS.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Bergland et al (2014) found evidence for dozens of genomic loci showing seasonal allele frequency changes in D. melanogaster that could not be explained by drift alone. Subsequent studies have expanded on those findings by leveraging seasonal population genomic data across multiple years from dozens of locations ( Kapun et al 2020 ; Machado et al 2021 ). Researchers have also sequenced museum specimens of the North American honeybee to study genomic changes in response to the introduction of a parasitic mite across roughly 50 generations ( Mikheyev et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described earlier, geological differences of genetic bias influence reproductive dormancy in D. melanogaster. Indeed, previous studies have shown that geographic variations in reproductive dormancy in wild D. melanogaster is associated with single nucleotide polymorphisms in the loci of tim, InR, FoxO, and couch potato (Williams et al, 2006;Sandrelli et al, 2007;Tauber et al, 2007;Paaby et al, 2010Paaby et al, , 2014Kolaczkowski et al, 2011;Lee et al, 2011;Fabian et al, 2012;Bergland et al, 2014;Kapun et al, 2016;Zhao et al, 2016;Betancourt et al, 2021;Machado et al, 2021). In the case of tim, it is hypothesized that the allelic frequencies of two distinct isoforms, ls-tim and s-tim (Rosato et al, 1997), may have evolved to cope with winter when D. melanogaster expanded into Europe (Tauber et al, 2007).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the wild, it has been well described that there are geographic variations in reproductive dormancy in D. melanogaster (Williams et al, 2006;Tauber et al, 2007;Sandrelli et al, 2007;Schmidt and Paaby, 2008;Emerson et al, 2009b;Kolaczkowski et al, 2011;Lee et al, 2011;Fabian et al, 2012;Bergland et al, 2014;Kapun et al, 2016;Zhao et al, 2016;Zonato et al, 2017;Lirakis et al, 2018;Betancourt et al, 2021;Machado et al, 2021). D. melanogaster originated in sub-Saharan Africa and subsequently expanded its habitat, possibly in association with humans and agriculture (Flatt, 2020).…”
mentioning
confidence: 99%
“…Metal toxicity can be induced simply by adding metals to fly food. Populations of D. melanogaster can be found across the globe allowing investigation of local adaptations and diversity [ 14 , 15 , 16 , 17 , 18 , 19 ]. Further, the small size and easy care of D. melanogaster translates into large sample sizes that include males, females, and a diversity of genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%